Precise evaluation of time-varying quadrupole field errors through closed-orbit measurements in the J-PARC main ring - Takashi Asami; Hideaki Hotchi; Susumu Igarashi; Tadashi Koseki; Yoichi Sato; Noboru Yamamoto; Takaaki Yasui (Physical Review Accelerators and Beams)
In the main ring (MR) of the Japan Proton Accelerator Research Complex, one of the primary sources of beam loss is the betatron resonance. A factor determining the strength of betatron resonances is the symmetry of optics, which relies on the quadrupole field errors in the ring. In the beam tuning of the MR, correcting quadrupole field errors plays a significant role in reducing beam loss. This paper introduces and examines a precise method to evaluate time-varying quadrupole field errors at individual quadrupole magnets around the ring through closed-orbit measurements in the MR. By applying this method, we experimentally determined substantial quadrupole field errors due to eddy currents on the vacuum ducts during acceleration. The methods developed in this paper are employed in the beam tuning for the user operations of the MR.